2015
DOI: 10.1007/s11332-015-0236-y
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in upper body strength and lower limb power of professional Italian firefighters

Abstract: Purpose Considering that the decrease in strength can be observed with ageing and that muscular endurance and strength are essential factors for firefighting effectiveness in critical situations, the purpose of this study was to evaluate the Upper Body Strength and Lower Limb Power of Professional of Italian Firefighters of 229 Italian male firefighters (age 32 ± 8 years, height 177 ± 6 cm, weight 79 ± 9 kg, BMI 24.5 ± 2.4 kg/m 2 ) and to compare the results in relation to the age (\30-year-old group; 31-to 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
3
9
1
Order By: Relevance
“…[ 35 ], which established that strength measures are able to explain a significant proportion of variation in firefighter ability test performance. The current findings, therefore, add further support to the importance of strength and more specifically to the testing and training of lower-body strength in operational firefighters [ 4 , 13 , 14 ]. Whilst practitioners should adopt a degree of caution interpreting estimated 1RM values, this novel approach to submaximal strength testing may offer sufficient validity to profile firefighter fitness effectively, without exposure to levels of fatigue associated with direct maximal testing.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…[ 35 ], which established that strength measures are able to explain a significant proportion of variation in firefighter ability test performance. The current findings, therefore, add further support to the importance of strength and more specifically to the testing and training of lower-body strength in operational firefighters [ 4 , 13 , 14 ]. Whilst practitioners should adopt a degree of caution interpreting estimated 1RM values, this novel approach to submaximal strength testing may offer sufficient validity to profile firefighter fitness effectively, without exposure to levels of fatigue associated with direct maximal testing.…”
Section: Discussionsupporting
confidence: 65%
“…Similarly, strength testing was limited to only the back-squat movement, so there would be value in establishing the relative validity of submaximal 1RM estimates across a range of upper and lower body lifts that may be relevant to the demands of firefighting (e.g. Overhead press, deadlift) [ 4 , 12 , 14 ]. Finally, whilst the reliability of the laser-optic device technology and associated maximal strength estimates used in the current study have been reported previously [ 18 ], there is a lack of firefighter-specific evidence relating to this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the female firefighters, Kirlin et al [23] have shown no significant differences across the age groups in the muscular fitness measured by the maximum number of push-ups, sit-ups, and back endurance. Results of our study about bench press test showed lower estimates and real values than Michaelides et al [66] and Perroni et al [68] in male firefighters.…”
Section: Plos Onecontrasting
confidence: 71%
“…To ensure the highest occupational efficiency, firefighters should maintain all measures of physical fitness through regular physical activity ( Durand et al, 2011 ; Yu et al, 2015 ; Nowak et al, 2018 ). In addition, it is well-documented that cardiorespiratory fitness, muscular strength, and endurance decline as firefighters age, due, in part, to a lack of leisure time physical activity and the natural decline in MSH as a product of the aging process ( Baur et al, 2012 ; Punakallio et al, 2012 ; Walker et al, 2014 ; Perroni et al, 2015 ; Frontera, 2017 ). This predisposes the firefighters to MSIs, especially, if they lack the necessary levels of physical fitness needed for firefighting.…”
Section: Discussionmentioning
confidence: 99%